The face of exile : autobiographical journeys - Melton, Judith M., 1941- (University of Iowa Press, 1998)
The rise of fascism in Europe created a body of works by authors for whom the choice of exile became the defining event in their lives, autobiographers who recounted terrifying stories of incarceration, fight, survival, and integration into a new culture. In The Face of Exile, Judith Melton offers a powerful and empathetic analysis of the autobiographies written by these unwilling participants in the social upheaval created by Hitler's war on Europe. In The Face of Exile, Judith Melton first focuses on the disrupted lives revealed in early memoirs by such self-defined witnesses of history as Li.